Health-Promoting Behaviors in Bulgaria: A Cross-Sectional Study on Non-Communicable Diseases and Lifestyle - Sophia Lazarova; Dessislava Petrova-Antonova (Societies)
(1) Background: Non-communicable diseases (NCDs) are a global health issue causing millions of deaths annually. Bulgaria has one of the highest rates of premature mortality due to NCDs in the European Union, mostly attributed to poor lifestyle habits. While adopting a healthy lifestyle is beneficial to preventing NCDs and managing existing conditions, research on health-promoting behaviors among individuals with NCDs remains limited. (2) Methods: This study investigates lifestyle disparities between individuals diagnosed with common NCDs and healthy individuals, and the sociodemographic determinants of healthy lifestyles among a nationally representative sample of 2017 adult Bulgarian citizens. We analyzed sociodemographic characteristics, health status (weight, height, existing diagnoses—diabetes, cardiovascular disease, insulin resistance, hypertension, and depression), and lifestyle data. (3) Results: Only 18.8% of the participants maintained a healthy lifestyle and 65% had a moderately healthy lifestyle. Over one-third of the respondents were pre-obese, and many reported having at least one chronic condition. Multinomial logistic regression revealed individuals with chronic conditions were less likely to have healthy or moderately healthy lifestyles compared to healthy participants, except those diagnosed with cardiovascular disease or depression, who were more likely to maintain healthy habits. (4) Conclusions: Considering the discovered discrepancies in lifestyle quality, more research should be directed toward identifying the barriers to healthy living for individuals diagnosed with NCDs.